Extending Our Promise: Providing Help to Mentally Ill Accused As Soon As Practicable - DeMelo, Cassandra (2019)
This thesis examines the current state of the criminal law’s interaction with mentally ill persons, with a specific interest in this interaction during pre-trial phases such as arrest and bail. It argues that the current provisions in the Criminal Code of Canada that allow for limited instances of pre-trial mental health assessments for adults are insufficient. The current options, including assessments to determine “not criminally responsible for reasons of mental disorder” or “fitness”, are not applicable in many situations. Other options available to accused outside of the Criminal Code are also lacking, as they are limited to the Mental Health Act, and the efforts of the sparsely situated mental health courts across the country. The focus for this paper is the resulting gap which leaves mentally ill persons untreated in their illness for longer than is necessary, thus increasing their chance of re-offending or breaching their court-imposed order – if they are given bail at all. This paper explores other potential options to assist mentally ill offenders who are in need of psychiatric intervention. One such option will be a comparison to the section 34 assessment option under the Youth Criminal Justice Act for those under 18 years of age. This discussion compares relevant legislation, leading case law, theoretical foundations and doctrinal legal scholarship with a hope of providing guidance for future legislation